Улаанбаатар хотын аэрозолийн оптик зузааны жилийн болон хоногийн явц - Г. , Батсүх; Ц., Баатарчулуун; Б. , Даариймаа (Scientific transaction of the National University of Mongolia. Physics, 2022)
We’ve determined that there is an approximately linearly increasing trend for the aerosol optical thickness (AOT) of the earth’s atmosphere when the solar elevation angle increases and the trend have been estimated for each season of a year. The sun’s elevation angle is dependent on a season and it also varies during day. In order to remove the dependence of AOT on solar elevation angle, we have introduced an idea that converting the aerosol optical thicknesses at given solar elevation angle to that of at a fixed elevation angle because the AOT has almost linear dependence on solar elevation angle. That scheme makes possibility of estimating daily and yearly trend of AOT and other optical parameters of air pollution.